2019
DOI: 10.12659/msm.917904
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Is Transformed into 1,25(OH)2D3 by Triggering CYP3A11(CYP3A4) Activity and Hydrolyzing Midazolam

Abstract: BackgroundVitamin D3 (VD3) is a commonly used supplement in clinical practice. Cytochrome P450 3A11 (CYP3A11) is the most important monomeric enzyme involved in metabolism of drugs. This study aimed to investigate effects of vitamin D3 (VD3) on CYP3A11 activity.Material/MethodsForty male Sprague-Dawley (SD) rats were randomly divided a Control group (peanut oil 0.1 ml/kg/d), a Low-VD3 group (100 IU/kg/d), a Medium-VD3 group (400 IU/kg/d), and a High-VD3 (1600 IU/kg/d) group. Blood samples were collected from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, it is not known if CYP3A11 has any vitamin D 25-hydroxylase activity. Recently, Zhu et al demonstrated that vitamin D3 treatment increases the levels of hepatic Cyp3a11 , and it was accompanied by high circulating plasma 25-OH-D and 1α,25(OH) 2 D levels ( 26 ). However, they did not measure the hepatic Cyp2r1 expression level ( 26 ), and the contribution of CYP3A11 to the increased 25-OH-D is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not known if CYP3A11 has any vitamin D 25-hydroxylase activity. Recently, Zhu et al demonstrated that vitamin D3 treatment increases the levels of hepatic Cyp3a11 , and it was accompanied by high circulating plasma 25-OH-D and 1α,25(OH) 2 D levels ( 26 ). However, they did not measure the hepatic Cyp2r1 expression level ( 26 ), and the contribution of CYP3A11 to the increased 25-OH-D is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhu et al demonstrated that vitamin D3 treatment increases the levels of hepatic Cyp3a11 , and it was accompanied by high circulating plasma 25-OH-D and 1α,25(OH) 2 D levels ( 26 ). However, they did not measure the hepatic Cyp2r1 expression level ( 26 ), and the contribution of CYP3A11 to the increased 25-OH-D is unclear. Interestingly, in our study, the hepatic Cyp3a11 level was positively and significantly correlated with the plasma 25-OH-D level.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been confirmed in our previous research that by activating CYP3A4 activity and hydrolyzing midazolam, VD3 can ultimately be transformed into 1,25(OH)2D3 [ 16 ]. In vitro studies showed that rifaximin can induce cytopigment P450 3A4 isoenzyme, but clinical studies have indicated that rifaximin has no obvious effect on drug metabolism [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%